As representações sobre a União Democrática Nacional na imprensa carioca do segundo governo Vargas (1951-1954) - Regina, Thiago Costa Juliani (2020)
This dissertation aims to analyze as part of the carioca press, through the newspapers Correio da Manhã, O Globo and Jornal do Brasil, represented the work of the União Democrática Nacional (UDN) in front of the Second Varga’s Government (1951-1954). Based on this theme and central objective, we seek to understand how these periodical perceived the role and tactics adopted by the UDN in the face of Getúlio's political proposals, which tried to count on the support of the party in several of the initiatives that left Palácio do Catete, despite of the party having constituted itself as the main force of opposition to its government. Consequently, we focus on the study of social representations in three topics: the composition of the “ministry of experience”; Administrative Reform; and, the process of creating Petrobras. These events were chosen because of the extensive participation of the “Brigadeiro’s party” in discussions about them. In all of these cases, in addition to being part of the debates, the UDN was also the subject of them, given that controversies arose over the line of action that the party should adopt in view of the government's plans. We also sought to identify what types of conceptions were discursively mobilized both to describe what the journals believed to be the party's attribution, and to portray their position on the relevant issues in dispute in the public debate. Furthermore, based on the recognition of these principles, on which the three newspapers built their representations, we sought to identify which trends were shared between the press and between them and the UDN, in particular on the theme of political participation in government projects for economic development. To fulfill this proposal, the methodology used was Content Analysis.